The Influence of Implementing Government Accounting Standards Based on Competence with The Use of Accounting Information Systems as A Moderation Variable - Kristiana, Ida; Erlangga , Ega Priyatna; Sinarasri , Andwiani (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: The implementation of accrual-based Government Accounting Standards (SAP) in Indonesia aims to enhance financial transparency and reliability following the issuance of Government Regulation No. 71 in 2010. Specific Background: In Central Java, while the provincial government has successfully adopted accrual-based SAP, discrepancies remain at district and city levels, affecting the attainment of Unqualified Opinions (WTP) on financial reports. Knowledge Gap: Previous studies have shown mixed results regarding the impact of Human Resource (HR) quality and Internal Control Systems on SAP implementation, with the moderating role of Accounting Information Systems (AIS) underexplored. Aims: This study investigates the influence of HR quality and Internal Control Systems on the successful implementation of accrual-based SAP, with AIS as a moderating variable, within the Central Java Provincial Government’s OPDs. Results: The study finds that HR quality positively impacts SAP implementation, while internal control systems do not. AIS weakens the relationship between HR quality and SAP success and does not moderate the effect of Internal Control Systems on SAP implementation. Novelty: This research highlights the unexpectedly weakening role of AIS in HR quality’s impact on SAP success, challenging existing assumptions about AIS’s moderating capabilities. Implications: The findings suggest a need for tailored AIS utilization strategies that consider specific contextual factors and HR characteristics, ensuring these systems enhance rather than hinder accrual-based SAP implementation in governmental contexts​.